Career Transitions: Varieties and Commonalities, - Louis, Meryl Reis (Academy of Management Review, 1980)
The effects of increasingly prevalent job and profession changing and re-evaluation of work vs. family priorities have led to a growing interest in careers issues. However, aids to understanding and managing career transition phenomena have not yet been developed. Toward that end, varieties of career transitions are identified here, and commonalities across transitions are explored.